Is ethical fashion the only socially approved fashion? A vision of anti-consumerist future in the behavior of fashion consumers - Perchla-Włosik, Aleksandra; Raciniewska, Alicja (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
This article presents a number of significant issues pertaining to how fashion consumers function in the field of ethical fashion. It is based on Polish and foreign literature of the subject and the findings of earlier qualitative studies – FGI, discourse analysis, and quantitative studies – the standardized interview questionnaire. Part one provides a discussion on the contemporary trends in consumer behaviour that fall within the spheres of anticonsumerism and deconsumption. Part two is based on the findings of a qualitative study conducted within the National Science Centre grant project, which explored how Polish fashion consumers perceive ethical fashion in the light of interdisciplinary fashion studies. Discourse analysis is also used to explore the sphere of fashion in Poland. For analysis purposes, respondents’ statements were categorized according to certain strategies, which are indicative of their consumer behaviours in the context of ethical fashion
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 501, s. 63-76
Keywords: ethical fashion; consumerism; consumer behaviour; fashion studies; konsumpcjonizm; zachowania konsumenckie; badania mody